Peptide profile of Parmigiano Reggiano cheese after simulated gastrointestinal digestion: From quality drivers to functional compounds - Castellone, Vincenzo; Prandi, Barbara; Bancalari, Elena; Tedeschi, Tullia; Gatti, Monica; Bottari, Benedetta (Frontiers in Microbiology, 2022)
Time of ripening has a strong impact in shaping the valuable and recognizable characteristics of long ripened cheeses such as Parmigiano Reggiano (PR) due to the interrelationship between microbiota and the proteolysis that occurs during ripening. The deriving peptide profile is linked to cheese quality and represents the canvas for enzymes upon digestion, which could be responsible for the release of potentially bioactive peptides (BP). In the present study we aimed at investigating the presence of BP in 72 PR cheese samples of different ripening times, from curd to 24 months of ripening, produced in 6 different dairies, and following their fate after simulated gastrointestinal digestion. A small number of peptide sequences sharing 100% similarity with known antimicrobial, antioxidant, and ACE-inhibitor sequences, were found in PR cheeses, while a higher number of potentially BP was found after digestion, in different amounts according to ripening time. Taking advantage of a complex organization of the sampling plan, we were able to follow the fate of peptides considered as quality drivers during cheese ripening to their release as functional compounds upon digestion.